# [March for reflection:|.Maynard] Martial of usage

[注：下文是群邮件的内容，标题是原有的。内容是学习一篇数学文章的笔记。]

["Terms of awareness /use" folded below] On going is to read a paper of primes to increase generic understanding on mathematics.[blog]

Seemingly plain usage might create high power at the right place.

♘   7          5

♗   2          3

Story - Armies were trained.

ℂ ℍ ℕ ℙ ℚ ℝ ℤ ℭ ℜ I|φ∪∩∈ ⊆ ⊂ ⊇ ⊃ ⊄ ⊅ ≤ ≥ Γ Θ Λ α Δ δ μ ≠ ⌊ ⌋ ∨∧∞Φ⁻⁰ 1

Recall that Sect.5 is of Fourier anaysis on digit functions. The task is to work out the detailed derivation ——

.

^gb^k (θ) = ∑(n) e(nθ)e(αsb(n)) ~> П(i)((ni)e(ni(α+b^i·θ)))

Shorthand notation: (n) refers to n < b^k;

(ni) refers to 0≤n0, ..., nk-1< b;

(i) refers to i = 0, ..., k - 1.

.

To be specific, set k = 2, b = 10. As such, "(n)" refers to sum of 99 +1 terms ——

(n) e(nθ)e(αsb(n)) =

e(0·θ)e(α·sb(0)) +

e(1·θ)e(α·sb(1)) +     e(2·θ)e(α·sb(2)) +     e(3·θ)e(α·sb(3)) + ...

+ e(28·θ)e(α·sb(28)) + e(29·θ)e(α·sb(29)) + e(30·θ)e(α·sb(30)) + ...

+ e(97·θ)e(α·sb(97)) + e(98·θ)e(α·sb(98)) + e(99·θ)e(α·sb(99)).

Note: n = 0 has to be included for a technical reason; see below.

.

---- Now, each instance of n is listed with better explicity.

---- Remember that the base b expansion of n = (i)ni·b^i is applied to each instance of n.

---- By definition, the digit function sb(n) = sb((i)ni·b^i ) = (i)ni.

---- There are two kinds* of instances of n in the above 99 terms.

---- # Take a look for the one* digit instance at first.

---- It is representative to take n = 3 for the instance of one digit* ——

---- 3 = n = (i)ni·b^i = n0·b^0 + n1·b^1 (with n0 = 3, n1 = 0 ).

---- sb(3) = sb(n) = sb((i)ni·b^i) = (i)ni = n0 + n1 = 3.

Note for stars: for the upper bound b^k, each number should be viewed as of k digits as one kind, crutial for a unified treatment.

---- Now consider the term ——

---- e(3·θ)e(α·sb(3)) = e((n0·b^0 + n1·b^1)·θ)e(α·(n0 + n1)) = e(n0(α + b^0·θ))·e(n1(α + b^1·θ)).

---- Apparently, for any instance of n of one digit, one has ——

---- e(nθ)e(αsb(n)) = e(n0(α + b^0·θ))·e(n1(α + b^1·θ)).

---- # Take a look for the two digit instance as follows.

---- It is representative to take n = 29 for the instance of two digits ——

---- 29 = n = (i)ni·b^i = n0·b^0 + n1·b^1.

---- sb(29) = sb(n) = sb((i)ni·b^i) = (i)ni = n0 + n1 = 9 + 2 = 11.

---- Now consider the term ——

---- e(29·θ)e(α·sb(29))

=  e((n0·b^0 + n1·b^1)·θ)e(α·(n0 + n1))

=  e(α·(n0 + n1)+(n0·b^0 + n1·b^1)·θ)

=  e(n0·(α + b^0·θ) + n1·(α + b^1·θ))

=  e(n0·(α + b^0·θ))·e(n1·(α + b^1·θ))

---- Apparently, for any instance of n of two digits, one has ——

---- e(nθ)e(αsb(n)) e(n0·(α + b^0·θ))·e(n1·(α + b^1·θ)).

Note: all instances of n are viewed as one kind, with the same form (cf. fruit and fruit).

.

(n) e(nθ)e(αsb(n)) =

e(0·θ)e(α·sb(0)) +

e(1·θ)e(α·sb(1)) +       e(2·θ)e(α·sb(2)) +     e(3·θ)e(α·sb(3)) + ...

+ e(28·θ)e(α·sb(28)) + e(29·θ)e(α·sb(29)) + e(30·θ)e(α·sb(30)) + ...

+ e(97·θ)e(α·sb(97)) + e(98·θ)e(α·sb(98)) + e(99·θ)e(α·sb(99)).

---- Replace the terms using the fruit and fruit with specific ni ——

(n) e(nθ)e(αsb(n))

e(0·(α + b^0·θ))·e(0·(α + b^1·θ))   ⬅ term for n = 0

e(1·(α + b^0·θ))·e(0·(α + b^1·θ))

e(2·(α + b^0·θ))·e(0·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(0·(α + b^1·θ))

e(0·(α + b^0·θ))·e(1·(α + b^1·θ))

e(1·(α + b^0·θ))·e(1·(α + b^1·θ))

e(2·(α + b^0·θ))·e(1·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(1·(α + b^1·θ))

e(0·(α + b^0·θ))·e(2·(α + b^1·θ))

e(1·(α + b^0·θ))·e(2·(α + b^1·θ))

e(2·(α + b^0·θ))·e(2·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(2·(α + b^1·θ))

.

.

.

e(0·(α + b^0·θ))·e(9·(α + b^1·θ))

e(1·(α + b^0·θ))·e(9·(α + b^1·θ))

e(2·(α + b^0·θ))·e(9·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(9·(α + b^1·θ)).

.

Now, let's see the grouped terms one by one ——

.

e(0·(α + b^0·θ))·e(0·(α + b^1·θ))   ⬅ term for n = 0

e(1·(α + b^0·θ))·e(0·(α + b^1·θ))

e(2·(α + b^0·θ))·e(0·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(0·(α + b^1·θ))

= [ e(0·(α + b^0·θ)) + e(1·(α + b^0·θ)) + e(2·(α + b^0·θ)) +...+ e(9·(α + b^0·θ)) ]·e(0·(α + b^1·θ))

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(0·(α + b^1·θ)).

.

e(0·(α + b^0·θ))·e(1·(α + b^1·θ))

e(1·(α + b^0·θ))·e(1·(α + b^1·θ))

e(2·(α + b^0·θ))·e(1·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(1·(α + b^1·θ))

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(1·(α + b^1·θ)).

.

e(0·(α + b^0·θ))·e(2·(α + b^1·θ))

e(1·(α + b^0·θ))·e(2·(α + b^1·θ))

e(2·(α + b^0·θ))·e(2·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(2·(α + b^1·θ))

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(2·(α + b^1·θ)).

.

e(0·(α + b^0·θ))·e(9·(α + b^1·θ))

e(1·(α + b^0·θ))·e(9·(α + b^1·θ))

e(2·(α + b^0·θ))·e(9·(α + b^1·θ))

...

e(9·(α + b^0·θ))·e(9·(α + b^1·θ)).

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(9·(α + b^1·θ)).

.

Now, we are arriving the target ——

(n) e(nθ)e(αsb(n)) =

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(0·(α + b^1·θ)) +

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(1·(α + b^1·θ)) +

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(2·(α + b^1·θ)) +

... ... ...

[ ∑(ni) e(ni·(α + b^0·θ))  ]·e(9·(α + b^1·θ))

[ ∑(ni) e(ni·(α + b^0·θ))  ]·[ e(0·(α + b^1·θ)) e(1·(α + b^1·θ)) + e(2·(α + b^1·θ)) +...+ e(9·(α + b^1·θ) ]

[ ∑(ni) e(ni·(α + b^0·θ))  ]·[ ∑(ni) e(ni·(α + b^1·θ)) ]

П(i)((ni)e(ni(α+b^i·θ)))

.

Note: looking at the final form, one realizes that the index i of b^i is fixed inside, not running with "(ni)". For the general case of k digits, the final form is viewed as ——

(ni)e(ni(α+b^0·θ)) ]·[ (ni)e(ni(α+b^1·θ)) ]· ... ·[ (ni)e(ni(α+b^k-1·θ)) ]

.

Comment: the final form is elegant, justifying the digital representation of n with leading zeros like 0...01 (=1). As the digit function sb(n) is involved in the Fourier transform, the final form is of a characteristic mode. It has to be a key finding.

ℂ ℍ ℕ ℙ ℚ ℝ ℤ ℭ ℜ I|φ∪∩∈ ⊆ ⊂ ⊇ ⊃ ⊄ ⊅ ≤ ≥ Γ Θ Λ α Δ δ μ ≠ ⌊ ⌋ ∨∧∞Φ⁻⁰ 1

.

https://blog.sciencenet.cn/blog-315774-1348654.html

## 全部精选博文导读

GMT+8, 2022-12-6 04:54